El fashion film, memoria de la moda y expresión posmoderna de la televisión digital - Uribe Wolff, María; Venditti, Stephanie (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
This article aims to conceptualize the emergence of fashion films as short films that facilitate the distribution of content on social networks, which are ideal for addressing transmedia advertising and trying to understand the converging scenarios that are part of it in the context of cultural digitization. The article reflects through different authors on the incursion of the fashion industry in digitization, its link with cinema, time, memory and platforms. Fashion films are studied as a bridge to venture into and revolutionize the expression and dynamics of movement understood within a contemporary social phenomenon.